KEAKTIFAN MAHASISWA STKIP WIDYA YUWANA DALAM MENGIKUTI PERKULIAHAN - Arnitasari, Niki Hartati; Gaudiawan, Antonius Virdei Eresto (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2019)
The activation of students in the lecture process is an essential task for students. Activation is the most important thing to develop student’s skills. In the learning process, students should play an active role and want to ask. Judging from the student STKIP Widya Yuwana inactivation is still lacking and still look low involvement as a student often they are reluctant to ask. Based on the background of the problem then formulated the problem formulation as follows: What is the liveliness of the lecture? What is the activation of STKIP Widya Yuwana students during this time? And what opportunities can be made to improve student activity in the lecture? The study used qualitative methods with data collection through interviews on six respondents conducted on the sixth to the thirteen April two thousand nineteen. The research instrument used is a variety of questions to know the meaning of the activation of students in the course, the activation of STKIP Widya Yuwana students in lectures and opportunities that can be made to improve student activity in lecturing.